UTM's chemical engineering pilot plant: a perspective - Abdul Aziz, Ramlan; Kamsah, Mohd Zaki; Ripin, Adnan; Ibrahim, Kamarul Asri (Institusi Jurutera Kimia Malaysia, 1992)
This paper discusses the establishment of UTM's chemical engineering pilot plant. Detail discussion is available in full text article.